Longman Academic Writing Series 5: Essays to Research Paper - P. M. Laurena, Olivia (Journal of Multidisciplinary in Social Sciences, 2023)
For English language learners in the university level, their skill in writing is one of the many important skills they need to learn and master, more specifically their academic writing skills. As students’ progress in developing their writing skills, the level of difficulty with regard to vocabulary, writing structures, and the process of writing compositions gets more and more complicated, formal and, in most cases, compositions become much longer. For some English language learners, the degree of difficulty can be doubled when instruction of academic writing is not thorough, detailed, or comprehensive.